2022
DOI: 10.21273/hortsci16334-21
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Organic Fertilizer Effects on Growth and Biomass of Lettuce Grown in a Soilless Production System

Abstract: Demand for locally produced, organically grown leafy greens is increasing throughout the United States. However, due to lack of efficient organic fertilizers (OFs) for soilless substrates, organic greenhouse production of leafy greens may be challenging. Therefore, a greenhouse study was conducted to analyze the effects of six liquid OFs on growth and development of lettuce in a soilless system. Two experiments were conducted using a randomized block design, and treatments included six fish- or plant-based OFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Further, El-Shinawy and Gawish (2006) showed that there was no significant difference in Chl of lettuce fertilized with different OFs and IFs in a hydroponic system. Shaik et al (2022) reported that lettuce plants fertilized with different OFs derived from different plant and animal sources resulted in no significant difference in Chl of lettuce compared with IF. In our study, most of the cases, the eggplant fertilized with different OFs and IFs resulted in similar Chl, which could be because these OFs were composed of different plant and animal sources with an adequate N content.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, El-Shinawy and Gawish (2006) showed that there was no significant difference in Chl of lettuce fertilized with different OFs and IFs in a hydroponic system. Shaik et al (2022) reported that lettuce plants fertilized with different OFs derived from different plant and animal sources resulted in no significant difference in Chl of lettuce compared with IF. In our study, most of the cases, the eggplant fertilized with different OFs and IFs resulted in similar Chl, which could be because these OFs were composed of different plant and animal sources with an adequate N content.…”
Section: Resultsmentioning
confidence: 99%
“…compared with IF. Results from the greenhouse experiment conducted by Shaik et al (2022) reported 18% to 30% reduction in lettuce yield while using various OFs compared with IFs. The authors concluded that the yield reduction in OF treatments was due to lower nutrient availability in OFs compared with IF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FAO estimates that annual world agricultural production needs to increase by 70% between 2005 and 2050 to feed the growing population (Conforti et al, 2011). In response to the current challenges facing feeding the populous urban residents, sustainable food production systems have emerged in urban areas (Shaik et al, 2022). Controlled Environment Agriculture (CEA) is defined as high-yield agriculture protected from the external environment (Armanda et al, 2019;Orsini et al, 2020), and can serve as an excellent solution for feeding the cities of the future (Thomaier et al, 2015).…”
mentioning
confidence: 99%